A methodology for fabrication of thermomechanically activated switchable surface wettability. Issue 42 (13th July 2016) - Laursen, Christopher M.; Brant, Jonathan A.; Frick, Carl P.
ABSTRACT: In this study a platform is laid out for the creation of a multitiered surface exhibiting switchable wettability. This is done through a combination of both an acrylate‐based polymer understructure photopolymerized into a pillared array, and selectively placed surface treatments on these pillars. The acrylate‐based polymer is created through a systematic study and is shown to exhibit drastic alterations in material stiffness over a 19 °C temperature transition under aqueous conditions, allowing for stiff, erect pillars in the low temperature state, and pliable pillars that can easily be bent in the high temperature state. The glass transition temperature and onset temperature for the polymer system is found to be 49 and 30 °C, respectively. Three different surface treatments, including trichloro(1H, 1H, 2H, 2H‐perfluorooctyl)silane, polydimethylsiloxane, and polydopamine, are investigated using static contact angle studies, and are selectively deposited onto the pillared surface such that a hydrophobic surface is exposed with the pillars erect, and a hydrophilic surface is exposed with the pillars in the bent state. The surface is shown to transition between first a hydrophobic, then hydrophilic state and return to a hydrophobic state when the investigations are coupled together forming a hierarchical surface structure. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44122. Abstract :